Nutritional characteristics of children with cerebral palsy. ARIE - Villa El Salvador, 2004 - Del Águila, Aníbal (2006)
Objective: To determine prevalence and types of malnutrition in children with cerebral palsy (CP) and to identify determinant problems. Design: Descriptive clinical study. Setting: Children's Medicine and Rehabilitation Centre ARIE, Villa El Salvador district. Patients: Fifty three children with CP receiving rehabilitation treatment. Interventions: Clinical information was obtained directly from the child's mother. Waterlow´s classification was used for nutritional status evaluation. Anemia was determined by hemoglobin and hematocrit levels and intestinal parasitosis by feces examination and Graham's test. Data was processed with SPSS 11,0. Main outcome measures: Malnutrition, feeding problems, gastroesophageal reflux, anemia, intestinal parasitosis. Results: Prevalence of malnutrition was 81,1% and chronic malnutrition was the most frequent diagnosis, in 43,5%. Disorders associated with malnutrition like feeding problems were present in 94,3% of children, and symptoms of gastroesophageal reflux disease in 81,1%. Prevalence of anemia was 32,4% and intestinal parasitosis was present in 54,1% of children. Conclusions: Children with cerebral palsy had a high prevalence of malnutrition frequently associated to feeding difficulties, gastroesophageal reflux and intestinal parasitosis. These children represent a high-risk group for morbidity and mortality.